Vitamin D significance in Combating; Progression and Austerity of COVID-19 - Umair Yaqub Qazi, (Pakistan Journal of Medical & Health Sciences, 2022)
Humankind on our planet is under high pressure at present, facing an alarming pandemic in the form of coronavirus infection 2019 (Covid-19), which is known to be stimulated by severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2). Covid-19 can lead to acute respiratory distress syndrome (ARDS). Due to the minimal treatments or research, it is essential to consider therapeutic strategies with immunomodulatory effects. According to past studies, supplementing with vitamin D has been shown to minimize or even prohibit respiratory infections in some situations, according to some studies. Recent research has also demonstrated an association concerning vitamin D imbalance and adverse COVID-19 outcomes. It is a debatable situation because vitamin D deficiency is an important health issue worldwide. There may be a benefit in supplementing the low vitamin D levels in COVID-19 infected persons to assist in preventing the disease from more complicating matters. Covid-19 may benefit from vitamin D's immunomodulatory properties, and a comprehensive examination of the effects of vitamin D on Covid-19 is outlined in this brief review.